Pengaruh Motivasi Spiritual Dan Gaya Kepemimpinan Spiritual Terhadap Kinerja Religius (Studi Kasus Pada Bmt.Mitra Mandiri Wonogiri) - Dewi, Zakhiya Roshita; , M.Sholahuddin, S.E.,M.Si (2016)
This study aims to determine the influence of spiritual motivation and spiritual leadership style to the performance of religious. This study uses quantitative techniques of data collection using questionnaires to measure data. This research was conducted in Wonogiri. And that became the object of research is all employees at BMT. Mitra Mandiri Wonogiri. The sample in this study were all employees working in BMT. Mitra Mandiri Wonogiri totaling 82 employees. Analysis of the data in this study using SEM parameter estimation using computer applications Partial Leas Square (PLS). Based on the survey results revealed that the spiritual motivation positive and significant influence on employee performance. The higher the spiritual motivation the higher the performance of employees. Spiritual leadership has a positive and significant impact on the performance of the religious. The better the spiritual leadership of the better performance of religious employees